Influence of Driver’s Experience on Textual Traffic Sign Efficiency Depending on Visibility - Pašagić, Senka; Pašagić, Jasmina; Ščukanec, Anđelko (Promet - Traffic&Transportation, 2012)
The research objective is to study the influence of thedriver’s experience on the efficiency of the textual traffic sign dependingon the visibility, that is on the weather conditions. Theresearch was canied out by simulating traffic situation for twodifferent visibility conditions (good and poor) on represmtativesample of drivers regardi11g their d1iving expe1ience.The research results indicate high dependency of traffic signefficiency on the driver’s experience. The textual traffic sign efficiencyis substantially lower in motorists with several years ofd1iving experience and the experienced motorists than thosewith less experience and extremely experienced mot01ists, whichis explained by motorist ’s evaluatio11 of the traffic sign significance.According to experimental results, less than 65% of driversin low visibility conditions registered the number of words onthe traffic sign, and less than 50% the precise content, thusleading to a conclusion that the traffic sign does not satisfy itsfunction in this situation.